Toxic and Microbiological Effects of Iron Oxide and Silver Nanoparticles as Additives on Extended Ram Semen - Ioannis A. Tsakmakidis; Theodoros Samaras; Sofia Anastasiadou; Athina Basioura; Aikaterini Ntemka; Ilias Michos; Konstantinos Simeonidis; Isidoros Karagiannis; Georgios Tsousis; Mavroeidis Angelakeris; Constantin M. Boscos (Animals, 2021)
The aim of the study was to investigate the effect of iron oxide (Fe) and silver (Ag) nanoparticles (NPs) on ram semen. A skim milk extender without antibiotics was used as a diluent of 21 ejaculates (8 rams; 2–3 ejaculates/ram). The groups of control (C; semen without NPs), Fe NPs (3.072 mg Fe3O4/mL semen), and Ag NPs (2.048 mg Ag-Fe/mL semen) were incubated (15 °C; 30 min), and then a magnetic field was used for NPs’ removal. Standard microbiological procedures were performed for all groups. Post-treated samples were stored (15 °C) for 24 h, and sperm variables (kinetics by computer assisted sperm analysis (CASA); viability; morphology; HOST; DNA integrity) were evaluated at 6 and 24 h. Semen data were analyzed by a mixed model for repeated measures and microbiological data with Student’s t-test for paired samples. At 6 h of storage, VCL and rapid movement-spermatozoa, and at 24 h, total/progressive motility and amplitude of lateral head displacement (ALH) were significantly decreased in group Ag compared to control. In group Fe, progressive/rapid movement-spermatozoa were significantly lower compared to control after 24 h of storage. Only in group Ag was a significant reduction of total bacterial count revealed. In conclusion, the examined Fe NPs demonstrated slight antibacterial effect, while the examined Ag NPs provided higher antibacterial properties accompanied by cytotoxicity.